2011
DOI: 10.5004/dwt.2011.1753
|View full text |Cite
|
Sign up to set email alerts
|

Potentially toxic trace elements accumulating in marine sediment and bivalves in the outfall area of a desalination plant

Abstract: 2011) Potentially toxic trace elements accumulating in marine sediment and bivalves in the outfall area of a desalination plant, Desalination and Water Treatment, 25:1-3, 106-112 To link to this article: http://dx. ab s t r ac tThis study evaluated the environmental impact of seawater desalination effluent discharged into a water body by investigating potentially toxic trace elements in the outfall area of a desalination facility on the southeastern coast of the Penghu Island (Taiwan). Trace element concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Potential ecological indicators of desalination to marine ecosystem investigation were conducted to describe biological damage to amphipod, bivalve, copepod, infauna, or the number of organisms which can be used for future report [90][91][92][93]. Previous studies have shown that the amphipod species Ampelisca brevicornis survival is a sensitive organism to assess the toxicity of contaminated sediment [94][95][96].…”
Section: Amphipod Bivalve and Copedodmentioning
confidence: 99%
“…Potential ecological indicators of desalination to marine ecosystem investigation were conducted to describe biological damage to amphipod, bivalve, copepod, infauna, or the number of organisms which can be used for future report [90][91][92][93]. Previous studies have shown that the amphipod species Ampelisca brevicornis survival is a sensitive organism to assess the toxicity of contaminated sediment [94][95][96].…”
Section: Amphipod Bivalve and Copedodmentioning
confidence: 99%